Bioaccumulation of Heavy Metals in Water, Sediments, and Tissues and Their Histopathological Effects on Anodonta cygnea (Linea, 1876) in Kabul River, Khyber Pakhtunkhwa, Pakistan. (6th March 2018) - Khan, Muhammad Iftikhar; Khisroon, Muhammad; Khan, Ajmal; Gulfam, Naila; Siraj, Muhammad; Zaidi, Farrah; Ahmadullah; Abidullah; Fatima, Syeda Hira; Noreen, Shumaila; Hamidullah; Shah, Zafar Ali; et al.
Abstract : The present investigation aimed to assess the concentrations of selected heavy metals in water and sediments and their bioaccumulation in tissues of freshwater mussels and their histopathological effects on the digestive gland, gills, and gonads of Anodonta cygnea . Water, sediments, and freshwater mussel samples were collected at four sites, that is, reference and polluted sites, along the Kabul River, Khyber Pakhtunkhwa. The polluted sites were receiving effluents from the industrial, agricultural, municipal, and domestic sources. The order of metals in the water wasZ n > P b > N i > C u > M n > F e > C r > C d, in sediments the order wasF e > Z n > C r > N i > M n > P b > C u > C d, and in the soft tissues the order wasF e > Z n > M n > P b > C u > C r > N i > C d . Histopathological alterations observed in polluted sites of Kabul River were inflammation, hydropic vacuolation, and lipofuscin pigments (in digestive gland), gill lamellar fusion, dilated hemolymphatic sinus, clumping, and generation of cilia and hemocytic infiltration (in gills), and atresia, necrosis, granulocytoma, hemocytic infiltration, and lipofuscin pigments (in gonads). The histopathological alterations in the organs of Anodonta cygnea can be considered as reliable biomarkers in biomonitoring of heavy metal pollution in aquatic ecosystems.